Sustainable agriculture in Ilha da Madeira - Portugal | Agricultura sustentável na Ilha da Madeira - Portugal - Souza Caldas, Raphael Miller de; Verslype, Nina Iris; Machado, José (Revista Geama, 2016)
Ilha da Madeira is an autonomous region of Portugal located in Atlantic Ocean, in center coordinates 32º43'N 17º43'O, is considered the largest island of archipelago of the same name. The island covers an area of 740 km². The island has many climate peculiarities mainly influenced by altitude and barriers formed by sharp reliefs, and that they provide North / South axis. Climate variability existing of the island is defined in two types temperate in north and subtropical climate in south. The part of North is cooler and wetter than the south, due to winds from North and end up having a barrier relief inherent to region. Since the year of 1419, the island was subject to various economic and agricultural cycles. Actually, the agricultural occupation of the territory is predominantly winery, horticultural and fruit production. The study was conducted from January to May 2016. Data in census institutes and scientific articles were compared for discussion. The data of production, area of cultivation were intertwined with sustainable agriculture like organic farming and possibilities was available for openings boundaries according to adjustment of the culture temperature, photoperiod and precipitation, and may contribute to increase economy and quality of life in island. The agriculture of the island is formed basically by agriculture family subsistence, involving more than 45,000 people, representing 20% of Madeira population resulting only 3% of the region's economy.